COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING - I Ketut R. Sudiarditha; Dewi Susita; Tri Mulyani Kartini (Faculty of Economics and Business, University of Pasundan, 2019)
This study aims to determine the effect of compensation and work discipline on employee performance through job satisfaction as an intervening. This research conduct at PT. XD Sakti Indonesia. The population is employees belonging to grade 2 (non-staff); The sample was taken, 200 respondents. Primary data and analyzed using Structural Equation Model (SEM). The results showed that compensation and work discipline had a positive and significant effect on employee performance through job satisfaction as an intervening. The findings of this study prove that compensation and work discipline have a positive and significant effect on job satisfaction, which can further improve employee performance. The independence of employees in performing has not been able to show their ability according to their duties and responsibilities, which is caused by the lack of employee confidence.